Pemetaan Bibliometrik dengan VOSviewer terhadap Tesis Program Studi Kebidanan Program Magister Universitas ‘Aisiyah tahun 2019-2022 - Irkhamiyati, Irkhamiyati; Kurniawan, Bagas Dwiki (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2024)
Research can change according to trends, and mapping is necessary to analyze changes. This research aims to map the thesis information of the Midwifery Master's Program at 'Aisyiyah University (UNISA) Yogyakarta from 2019-2022 based on bibliometric analysis. This quantitative descriptive study relies on secondary data from the publications of master's theses in Midwifery at UNISA Yogyakarta from 2019 to 2022. Researchers sampled 170 thesis titles in this study, conducted at the UNISA Yogyakarta Library from December 2022 to May 2023. The research identifies the distribution of student theses, the correlation between research keywords, historical research trends based on keywords, and the density of fields in theses. This research uses VOSviewer as software to analyze the data. According to the DDC, the results show 13 clusters based on a 2-keyword limit and 23 subject groups. Co-occurrence analysis identifies 11 critical keywords. Visualization overlays show shifts in research trends from year to year, while density results highlight COVID-19, pregnancy, knowledge, and breastfeeding. Based on the above results, researchers can conclude that the most researched trends from 2019-2022 are COVID-19, pregnancy, breastfeeding, and experience. Meanwhile, research subjects that could be options for further research are hypertension in pregnancy, women's depression, adolescence, anemia, and primipara. Suggestions for further research include adding topics that have yet to be extensively studied as options for research to expand and diversify the number of themes explored.